Assessing the benefits of horizontal collaboration using an integrated planning model for two-echelon energy efficiency-oriented logistics networks design. Issue 3 (3rd July 2022) - Aloui, Aymen; Hamani, Nadia; Derrouiche, Ridha; Delahoche, Laurent
Abstract : The transition to modern and ecologically oriented industries requires the application of new approaches and advanced models of logistics management. In this context, horizontal collaboration has recently become a promising and emerging practice for companies intending to improve their freight transportation efficiency and achieve environmental sustainability. This strategy is usually involved in the independent planning of decision-making problems with economic objectives. However, integrated optimisation of planning decisions with environmental considerations is nowadays considered as one of the major challenges to enhance the competitiveness of logistics networks. In this paper, the integrated planning problem of location, inventory and routing to design two-echelon green logistics networks is studied in collaborative and non-collaborative scenarios. The main purpose of this study is to assess the benefits of horizontal collaboration between suppliers in integrated freight transportation optimization by proposing a new decision support tool. A bi-objective Mixed Integer Linear Programming is proposed and adapted to address both distribution strategies. First, a resolution of the several scenarios with a single objective and a comparison of the results are performed. Second, a multi-objective optimization using an aggregation approach is conducted to find a good trade-off between the economic objectives and environmental ones. The experimental results show that horizontal collaboration among suppliers may decrease the total aggregated cost and emissions in the logistics system.